2022
DOI: 10.1007/s40544-021-0552-y
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-induced nanoscale friction modulation on piezoelectric materials

Abstract: Mechanical vibration, as an alternative of application of solid/liquid lubricants, has been an effective means to modulate friction at the macroscale. Recently, atomic force microscopy (AFM) experiments and model simulations also suggest a similar vibration-induced friction reduction effect for nanoscale contact interfaces, although an additional external vibration source is typically needed to excite the system. Here, by introducing a piezoelectric thin film along the contact interface, we demonstrate that fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It means that periodic textured surfaces and atomically flat surfaces have similar functions in terms of modulating friction force. Since our studies above and those of many others have shown that the application of excitation at the resonant frequencies of the frictional system can reduce the friction force, here we directly fix the excitation frequency at the washboard frequency. Figure c clearly shows that the friction force changes periodically at washboard frequency as the initial phase angle φ increases gradually from 0 to 360°.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It means that periodic textured surfaces and atomically flat surfaces have similar functions in terms of modulating friction force. Since our studies above and those of many others have shown that the application of excitation at the resonant frequencies of the frictional system can reduce the friction force, here we directly fix the excitation frequency at the washboard frequency. Figure c clearly shows that the friction force changes periodically at washboard frequency as the initial phase angle φ increases gradually from 0 to 360°.…”
Section: Resultsmentioning
confidence: 99%
“…These groundbreaking experiments open the door to superlubricity, a state with a friction coefficient of less than 0.01 between two rubbing surfaces. , Shortly thereafter, superlubricity is recognized as the ultimate solution to protect various mechanical systems from malfunctions caused by friction and wear. , Recently, many researchers in the community have conducted theoretical and experimental investigations on superlubricity. Several techniques and experimental strategies have been proposed to achieve superlubricity, such as the incommensurate surface , and the application of mechanical vibrations. However, there is still a scientific gap between the proposed superlubricity technology and practical engineering application due to the complexity of friction and energy dissipation involved in the buried interface …”
Section: Introductionmentioning
confidence: 99%